Między kulturą wysoką a kulturą popularną. O muzyce George'a Gershwina w „Manhattanie” Woody'ego Allena - Pomostowski, Piotr (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2013)
The article focuses on the relationships between high culture and popular culture in relation to film music. To this end, the author conducted a thorough analysis of the works of George Gershwin used in Woody Allen’s film Manhattan. The article consists of two parts and a conclusion. In the first part, the author presents a brief history of the continuous grinding together of high and popular culture in music, resulting in symphonic jazz, which came about in the 1920s, and whose precursor was George Gershwin. The second part is a cinematic and musicological analysis of all the works of Gershwin appearing on the soundtrack of Manhattan, and an attempt to find associations between the director and composer. In conclusion, the author notes that the phenomenon of mixing of popular culture and mass culture (both on the music, as well as its use in the work of the film) is subordinated in both George Gershwin and Woody Allen’s work to attempts to find their own identity, and one of the sources of inspiration of both artists is the same New York City, which is a city-myth.

Tematem artykułu są relacje zachodzące pomiędzy kulturą wysoką a kulturą popularną w odniesieniu do muzyki filmowej. W tym celu autor przeprowadza wnikliwą analizę utworów George'a Gershwina wykorzystanych w filmie Manhattan Woody'ego Allena. Artykuł składa się z dwóch części i konkluzji. W części pierwszej autor przedstawia krótką historię ciągłego ścierania się ze sobą kultury wysokiej i popularnej na gruncie muzycznym, czego efektem jest, powstały w latach dwudziestych XX wieku jazz symfoniczny, którego prekursorem jest George Gershwin. Część druga to filmoznawczo-muzykologiczna analiza wszystkich utworów Gershwina, pojawiających się na ścieżce dźwiękowej filmu Manhattan i próba znalezienia powiązań między osobami reżysera i kompozytora. W konkluzji autor artykułu zauważa, że zjawisko mieszania się kultury popularnej i kultury masowej (zarówno na gruncie samej muzyki, jak i jej wykorzystaniu w dziele filmowym) podporządkowane jest w twórczości Georege'a Gershwina i Woody'ego Allena próbie odnalezienia własnej tożsamości, a jednym ze źródeł inspiracji dla obu artystów jest sam Nowy Jork, który staje się miastem-mitem.
Between high culture and popular culture. The music of George Gershwin in Manhattan by Woody Allen
Keywords: high culture; popular culture; film music; Woody Allen; George Gershwin; Manhattan; symphonic jazz; identity; New York City; composer; director; kultura wysoka; kultura popularna; muzyka filmowa; jazz symfoniczny; tożsamość; Nowy Jork; kompozytor; reżyser